Antioxidant and Antiradical Activity of Beetroot (Beta vulgaris L. var. conditiva Alef.) Grown Using Different Fertilizers - Aynur Babagil; Esen Tasgin; Hayrunnisa Nadaroglu; Haluk Caglar Kaymak (Journal of Chemistry, 2018)
Fertilizers in different nitrogen forms (calcium ammonium nitrate (CAN), urea, ammonium sulfate (AS), and ammonium nitrate (AN)) and their doses (50, 100, and 150) for beetroot (BT) (Beta vulgaris L. var. conditiva Alef.) and the antioxidant and antiradical activities in the lyophilized water and alcohol extracts of BT were evaluated. In order to evaluate antioxidant and radical removing activities of BT roots, total phenolic compound amount assignment, total flavonoids amount assignment, method of Fe3+-Fe2+ reduction activity using ferric cyanate reduction, cupric ions (Cu2+) reducing capacity with CUPRAC method, Fe3+ reducing capacity according to FRAP method, ferrous ions (Fe2+) chelating activity, superoxide anion radical (O2•-) removing activity, and 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS•+) radical removing activity were determined. In the study, BHA and α-tocopherol were used as standard antioxidants. It was determined that water and alcohol extracts obtained from BT roots indicated reduction activities, effectively. In addition, it was also determined that these reduction activities were indicated in most BT roots grown in fertilizer media at lower percentage and that they had higher antioxidative level than that of standard antioxidants.